MILITARY ASSISTANCE OF THE NORDIC COUNTRIES TO UKRAINE IN 2022–2025 IN THE CONTEXT OF THE FORMATION OF A REGIONAL DETERRENCE SYSTEM - Myronov, Illia (Public Management and Policy, 2026)
The article examines the evolution of Nordic military assistance to Ukraine in 2022–2025 within the broader transformation of the security environment in Northern Europe. It analyses how Denmark, Sweden, Norway, Finland, and Iceland moved from emergency transfers of weapons and financial-logistical support to a more complex model combining the delivery of heavy systems, military training, multi-year financial instruments, capability coalitions, and defence-industrial cooperation. Drawing on comparative, historical-chronological, and institutional analysis, the study shows that this transformation developed in parallel with Finland’s and Sweden’s accession to NATO, the strengthening of NORDEFCO, the expansion of Nordic-Baltic coordination, and the growing role of multilateral frameworks for supporting Ukraine. The article argues that Nordic military assistance has a dual strategic effect: it strengthens Ukraine’s defence capacity through expanded combat capabilities, personnel training, and support for the reproduction of defence potential, while also contributing to the densification of a regional deterrence framework within the Nordic-Baltic and Euro-Atlantic security space. It concludes that in 2022–2025, support for Ukraine became for the Nordic countries not only an instrument of external assistance, but also a practical mechanism for implementing a new model of regionally concentrated allied security.